A PRELIMINARY INVESTIGATION ON CHANGING TEMPERATURE MAXIMA-MINIMA DEVIATION (TMIN-MAX DEVIATION) IN INDONESIA - Djoko Harmantyo (Indonesian Journal of Geography, 2011)
While the immediate impacts of climate change have been widely discussed,there are only few researches on climate change revealing its effect to temperatureamplitude. Changing temperature amplitude will hamper metabolism process,which in turn will decrease productivity and, even, cause the extinction of certainorganism species. This research will expose the changing temperature amplitude (Tminmax)including its trend pattern in Indonesia. The adoption of trend analysis methodand comparison analysis to the values of temperature amplitude in 60 AWS stationfrom 1980-2007 indicates upward trend of annual mean temperature with shortertemperature amplitude. This shorter temperature amplitude is characterized byannual mean temperature maxima increase less than the rise of annual meantemperature minima. Data analysis finds indication, i.e. the more eastward direction, thegreater difference of average Tmin-max deviation. Yet, this research fails to show whatfactors contributing to the changing temperature amplitude. More in-depth researchof these factors at ecological scale will be necessary as crucial part in determiningadaptation programs to this on-going climate change phenomenon.